Kruppel-like factor 8 regulates triple negative breast cancer stem cell-like activity - Le Minh, Giang; Esquea, Emily M.; Dhameliya, Tejsi T.; Merzy, Jessica; Lee, Mi-Hye; Ball, Lauren E.; Reginato, Mauricio J. (Frontiers in Oncology, 2023)
Breast cancer is one of the most common cancers in women. Breast tumor development is regulated by a sub-population of breast cancer cells, termed cancer stem-like cells (CSC). CSCs share characteristics of mammary stem cells, capable of self-renewing and differentiating, and are involved in promoting breast cancer invasion, metastasis, drug resistance and relapse. CSCs are highly adaptable, capable of reprogramming their own metabolism and signaling activity in response to stimuli within the tumor microenvironment. Recently, the nutrient sensor O-GlcNAc transferase (OGT) and O-GlcNAcylation was shown to be enriched in CSC populations, where it promotes the stemness and tumorigenesis of breast cancer cells in vitro and in vivo. This enrichment was associated with upregulation of the transcription factor Kruppel-like-factor 8 (KLF8) suggesting a potential role of KLF8 in regulating CSCs properties. Here, we show that KLF8 is required and sufficient for regulating CSC phenotypes and regulating transcription factors SOX2, NANOG, OCT4 and c-MYC. KLF8 levels are associated with chemoresistance in triple negative breast cancer patients and overexpression in breast cancer cells increased paclitaxel resistance. Importantly, KLF8 and OGT co-regulate each other to form a feed-forward loop to promote CSCs phenotype and mammosphere formation of breast cancer cells. These results suggest a critical role of KLF8 and OGT in promoting CSCs and cancer progression, that may serve as potential targets for developing strategy to target CSCs specifically.